An intuitive computational multi-scale methodology and tool for the dynamic modelling of viscoelastic composites and structures. (1st June 2016) - El Hachemi, M.; Koutsawa, Y.; Nasser, H.; Giunta, G.; Daouadji, A.; Daya, E.M.; Belouettar, S.
Abstract: This paper proposes an intuitive computational multi-scale homogenisation procedure and tool for the estimation of the effective static and mechanical properties of complex viscoelastic composite material and structures. The proposed solution consists in computing numerically the complex effective properties (storage and loss moduli) as function of frequency. The developed numerical tool is coupled with ABAQUS FEA in order to ease the uptake of the technology code and allows for an accurate and automatic simulation of composite engineering structures with substantially less human intervention and a rational control of the error. Details concerning the numerical implementation and a selection of representative numerical examples are provided.